Insights into the Key Genes in Cucumis melo and Cucurbita moschata ToLCNDV Resistance - Belén Román; Pedro Gómez; Dirk Janssen; Leticia Ruiz (Horticulturae, 2023)
Tomato leaf curl New Delhi virus (ToLCNDV, family Geminiviridae, genus Begomovirus) is a whitefly-transmitted virus that causes widespread damage in Cucurbitaceae and Solaneceae crops worldwide. The Spanish strain, ToLCNDV-ES, affects mainly cucurbit crops and has spread through the Mediterranean basin since its first detection in 2013 in the south of Spain. The control of the virus has been based on the adoption of measures to control the vector, which have not been sufficient to reduce production losses. Therefore, the identification of key genes for ToLCNDV resistance is essential for the development of resistant plants. Regarding genetic control of resistance in cucurbit crops, one major locus on chromosome 11 and two additional regions in chromosomes 12 and 2 of C. melo linked to ToLCNDV resistance have been described recently. Concerning C. moschata, a major QTL was also identified on chromosome 8 that resulted in synteny with a QTL on chromosome 11 of C. melo. In this work, we investigated the molecular basis of ToLCNDV resistance in contrasting accessions of C. melo and C. moschata by transcriptional characterization of 10 different candidate genes controlling host factors related to proviral or antiviral mechanisms. Two proviral factor genes, ARP4 in C. melo and SYTA in C. moschata, showed clear differences in expression levels when the susceptible and resistant accessions were compared. The knowledge of proviral factors associated with resistance could be used to screen an active mutagenesis TILLING platform. This is the case of C. pepo, in which no ToLCNDV resistance has been described to date. The relationship between the regulation of the genes ARP4 and SYTA, as well as the genome position of the described loci related to ToLCNDV resistance, is also discussed.